Nanostructures and nanotechnology - Natelson, Douglas, 1970- (Cambridge : Cambridge University Press, 2015)
Focusing on the fundamental principles of nanoscience and nanotechnology, this carefully developed textbook will equip students with a deep understanding of the nanoscale. Each new topic is introduced with a concise summary of the relevant physical principles, emphasising universal commonalities between seemingly disparate areas, and encouraging students to develop an intuitive understanding of this diverse area of study Accessible introductions to condensed matter physics and materials systems provide students from a broad range of scientific disciplines with all the necessary background Theoretical concepts are linked to real-world applications, allowing students to connect theory and practice Chapters are packed with problems to help students develop and retain their understanding, as well as engaging colour illustrations, and are accompanied by suggestions for additional reading. Containing enough material for a one- or two-semester course, this is an excellent resource for senior undergraduate and graduate students with backgrounds in physics, chemistry, materials science and electrical engineering.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Nanostructured materials